Compound Imaging Technology and Echogenic Needle Design: Effects on Needle Visibility and Tissue Imaging. Issue 5 (1st September 2013) - Wiesmann, Thomas; Bornträger, Andreas; Zoremba, Martin; Neff, Martin; Wulf, Hinnerk; Steinfeldt, Thorsten
Abstract : Introduction: Needle visualization in ultrasound-guided regional anesthesia can be improved by using needles of echogenic design with higher rate of reflection of ultrasound waves. Imaging solutions such as compound imaging might further improve imaging of both needle and tissue; these effects have not yet been studied. We hypothesized that compound imaging would significantly improve needle visibility, regardless of the insertion angle or needle type used. The effects of compound imaging on needle artifacts and tissue imaging were also investigated. Methods: A total of 200 video clips of in-plane needle insertions were obtained in embalmed cadavers with a conventional needle and an echogenic needle at 5 different insertion angles, with both conventional B-mode ultrasound imaging and compound imaging technology. Visibility of the needle shaft and needle tip as well as the needle artifact rate were assessed by a blinded investigator on a 4-point ordinal scale. The effects on tissue image quality and speckle artifacts were also assessed. Stepwise linear regression was performed to differentiate effects on needle visibility scores. Results: Imaging of the needle shaft and tip was significantly enhanced when compound imaging technology was used ( P < 0.0001). Use of echogenically designed needles or shallow needle insertion angles improved visibility of both shaft and tip (both P < 0.0001). With compound imaging, there are fewer needle artifacts, and tissue imaging quality and speckle artifact rate are significantly improved. Conclusions: Compound imaging technology enhances needle imaging with both echogenic and conventional needles. Tissue imaging and speckle artifacts are also optimized. Echogenic needle design results in better needle visibility scores in both B-mode and compound imaging.